Penggunaan Direct Instruction pada Pembelajaran Menerapkan Sifat-sifat Cahaya dan Keterkaitannya dengan Indera Penglihatan di Kelas IV SD - Friska Efendi (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2019)
The background of the research was the low learning outcomes of students on natural science course in fourth grade of SD Negeri 07 VII Koto Sungai Sariak. This was caused by uninteresting and irrelevant media, methods or model applied by teachers to deliver the materials. This study aimed to describe the influence of the use of direct instruction model to the material of applying the light characteristics and its association with sense of sight. 56 students involved in this experiment with one experimental class and one control class. The sampling was collected using saturated sampling technique so it was chosen class IV.1 as experimental class and class IV.2 as control class. From the research, it was found that the implementation of direct instruction model gave positive impact to the students’ learning outcomes. In addition, this model also influenced the attitude dimensions which have been mentioned on observation sheet.